Research on the Technique of Piano Adaptation: -- Take the Sorrow of Love as an Example - Jiao, Lixiang (Transactions on Social Science, Education and Humanities Research, 2023)
Sergey Vilievich Rahmaninov Sergei Vassilievitch Rachmaninoff (1873-1943) is a classical music composer, pianist and conductor in the 20th century. This paper focuses on the creation techniques of Rachmaninov's piano adaptation of Chrysler's "sadness of Love", and explores the techniques of its own adaptation characteristics presented in this adaptation. This paper discusses the inheritance and development of traditional harmony in Rachmaninov's creation and adaptation techniques, and makes the musical analysis of Rachmaninov's piano adaptation through the characteristic analysis of Chrysler's Sorrow of Love. This article is divided into three chapters, the first chapter is the adaptation of the music, and a brief description of the music adapted by Rachmaninov. The second chapter is based on the analysis of the creative concept contained in the Rachmaninov's adaptation, which is specifically the common technical features in the adaptation. The third chapter is the analysis of the features of Rachmaninov's adaptation "The orrow of Love". Finally, rachmaninov's inheritance and development of traditional harmony are summarized.